2016
DOI: 10.1093/bmb/ldw015
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease and household air pollution from use of solid fuel: a systematic review

Abstract: The need for such research is particularly pressing because the incidence of CHD in developing countries is rising, and IAP may interact synergistically with the risk factors that are driving that increase. Furthermore, relatively cheap methods are available to reduce IAP from use of solid fuels, and there are indications from intervention studies that these may impact beneficially on CHD as well as other diseases caused by such pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 40 publications
1
50
1
Order By: Relevance
“…44 Like us, Dratva et al reported stronger effect among diabetics. 19 Indoor air pollution, a risk factor for CVD per se 45 , emerged as an important factor aggravating the effect of noise. Taking BP-lowering medication seemed to buffer the effect of RTN in our study, while Foraster et al did not evidence a signifi cant interaction.…”
Section: Findings On Noise and Blood Pressurementioning
confidence: 99%
“…44 Like us, Dratva et al reported stronger effect among diabetics. 19 Indoor air pollution, a risk factor for CVD per se 45 , emerged as an important factor aggravating the effect of noise. Taking BP-lowering medication seemed to buffer the effect of RTN in our study, while Foraster et al did not evidence a signifi cant interaction.…”
Section: Findings On Noise and Blood Pressurementioning
confidence: 99%
“…Adjusted odds ratio (OR) was generated through multivariate logistic regression models.results Of 495 participants, 356 (72%) were women and 474 (95.8%) were receiving antiretroviral therapy (ART). The median age (years) [interquartile range (IQR)] was 43 [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. The overall prevalence of MS per NECP/ATP III and IDF criteria was 27% [95% CI: 20-35%] or 30% [95% CI: 23-38%], respectively.…”
mentioning
confidence: 99%
“…While the Global Burden of Disease Study estimated the global impact of household air pollution due to biomass fuel use based on the observed relationship between ambient air pollution exposure and cardiovascular events, very few studies have examined cardiovascular outcomes in biomass fuel users. Emerging data suggest an association between biomass fuel use and coronary heart disease 109 . In a study of participants living in the Brazilian Amazon, elderly individuals with increased exposure to biomass fuel smoke had increased cardiovascular mortality when compared to age-matched controls 110 .…”
Section: Household Air Pollution From Biomass Fuel Usementioning
confidence: 99%